Neck circumference is a better correlate of insulin resistance markers than other standard anthropometric indices in patients presenting severe obesity. Issue 4 (July 2022) - Scovronec, Anaïs; Provencher, Amélie; Iceta, Sylvain; Pelletier, Mélissa; Leblanc, Vicky; Nadeau, Mélanie; Simard, Serge; Biertho, Laurent; Richard, Denis; Tchernof, André; Michaud, Andréanne
Abstract: Background: Previous studies have demonstrated stronger associations between metabolic alterations and neck circumference (NC) than with body mass index (BMI) or waist circumference (WC). However, most of these studies were performed in individuals presenting overweight or mild obesity. Objective: To determine which adiposity index among BMI, WC, NC and fat mass (FM) can best predict metabolic alterations in men and women presenting severe obesity. Methods: Anthropometric and plasma biochemical parameters were measured in 81 participants presenting severe obesity (19 men, 62 women; age: 44.5 ± 8.9 years; BMI: 43.5 ± 4.1 kg/m 2 ). Multiple linear regressions were used to determine the best predictors of metabolic alterations among each adiposity index. Results: NC was positively correlated with fasting insulin concentrations, C-peptide concentrations and HOMA-IR values and negatively correlated with HDL-C concentrations. NC was the best predictor of glucose homeostasis indices and HDL-C concentrations in models also including sex, BMI, WC, and FM. The ROC curve analysis indicated that a NC ≥ 37.8 cm best predicted type 2 diabetes. Conclusions: NC seems a better predictor of insulin resistance and lower HDL-C concentrations in patients presenting severe obesity compared to other standard anthropometric indices, and particularly in women. The small sample size in men prevent us to draw clear conclusions. NC could be useful in targeting patients with metabolic alterations who could benefit from medical or surgical treatment of obesity. Highlights: Neck circumference as a marker of metabolic alterations in patients presenting severe obesity. NC is a better predictor of insulin resistance in these patients compared to other standard anthropometric indices. NC could be useful in targeting patients with metabolic alterations who could benefit from bariatric surgery.